6 - Mayi-Mayi: Young Rebels in Kivu, DRC - Jourdan, Luca (Africa Development, 2021)
Mayi-Mayi militias have played a central role in the Congo war. Mostly active in North and South Kivu, these rural militias are not a unified movement. Nevertheless, they share a nationalist ideology and a number of war rituals centered on the belief that the mayi, a specially treated water, can protect warriors from bullets. In this article, I have traced the history of these beliefs and ritual practices that are rooted in the pre- colonial and colonial periods. Far from being a symptom of regression or new-barbarism, I have tried to show that the recourse to war rituals, as well as the nationalistic discourse, were effective in compensating the lack of weapons and military organization, and in mobilizing youth in a context of state collapse. Nevertheless, most of Mayi-Mayi com- manders have proved to be opportunists and many young people have become involved in a spiral of violence that needs to be broken.